Interactions between deliberation and delay-discounting in rats - Papale, Andrew E. (2012)
When faced with decisions, rats sometimes pause and look back and forth between possible alternatives, a phenomenon termed vicarious trial and error (VTE). When it was first observed in the 1930s, VTE was theorized to be a mechanism for exploration. Later theories suggested that VTE aided the resolution of sensory or neuroeconomic conflict. In contrast, recent neurophysiological data suggest that VTE reflects a dynamic search and evaluation process. These theories make unique predictions about the timing of VTE on behavioral tasks. We tested these theories of VTE on a T-maze with return rails, where rats were given a choice between a smaller reward available after one delay or a larger reward available after an adjustable delay. Rats showed three clear phases of behavior on this task: investigation, characterized by discovery of task parameters; titration, characterized by iterative adjustment of the delay to a preferred interval; and exploitation, characterized by alternation to hold the delay at the preferred interval. We found that VTE events occurred during adjustment laps more often than during alternation laps. Results were incompatible with theories of VTE as an exploratory behavior, as reflecting sensory conflict, or as a simple neuroeconomic valuation process. Instead, our results were most consistent with VTE as reflecting a search process during deliberative decision making. This pattern of VTE that we observed is reminiscent of current navigational theories proposing a transition from a deliberative to a habitual decision-making mechanism.